E0691 Feasibility and reproducibility of a new semiautomated quantification of left ventricular volumes and ejection fraction in normal adults using real time 3-dimensional echocardiography. (17th November 2010) - Yuman, Li; Mingxing, Xie; Xinfang, Wang; Qing, Lv; Li, Yuan; Lan, Jiang; Yue, Song; Ning, Zhang
Abstract : Objective: We sought to investigate the feasibility and reproducibility of the new semi-automated tool (4DLVQ) quantification of left ventricular (LV) volumes and ejection fraction (EF) compared to standard 3D echo tool (TomTec 4D LV-Analysis) using real time 3-dimensional echocardiography. Methods: Real time 3D echocardiography examinations were performed in 24 volunteers. In the apical 3D full-volumetric images, LV end-diastolic volumes (EDV), end-systolic volumes (ESV) and EF were measured using 4DLVQ and TomTec. The repeatability and agreement of the new method were evaluated compared to TomTec. Results: 1. The analysis time of 4DLVQ was significantly shorter than for TomTec (156.63±33.72 s vs 275.55±50.64 s, p<0.05). 2. There were no significant difference in LVEDV (75.40±16.72 ml vs 71.65±14.81 ml), LVESV (30.25±6.69 ml vs 28.30±6.71 ml) and LVEF (59.65±4.96% vs 60.70±3.51%) between the two methods (p>0.05). 3. LVEDV, LVESV and LVEF measured by 4DLVQ had good correlation with those by TomTec. (r1 =0.715, r2 =0.618 r3 =0.532, respectively, p<0.05 for all). 4. Bland-Altman analysis revealed high agreement in LV volume and EF between 4DLVQ and TomTec, with 95% limits of agreement of −19.8∼27.3 ml, −9.5∼13.4 ml and −9.4∼7.3% for EDV, ESV, and EF respectively. Comparison with TomTec, 4DLVQ showed lower intraobserver and interobserver variabilities, Intra-observer variability of 4DLVQ versus TomTec was 12.29% versus 21.96% for EDV, 16.92% versus 34.35% for ESV, and 6.50% versus 7.24% for EF. Inter-observer variability of 4DLVQ versus TomTec was 9.84% versus 18.13% for EDV, 10.47% versus 25.12% for ESV, and 6.50% versus 6.72% for EF. In comparison with TomTec, 4DLVQ showed higher intra-class correlation coefficient. Conclusions: 4DLVQ is a novel, simple, feasible and reproducible tool for LV volumes and EF.